2008
DOI: 10.1634/stemcells.2007-0724
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Enhances Tumor Stemness by Increasing the Invasive and Tumorigenic Side Population Fraction

Abstract: Although advances have been made in understanding the role of hypoxia in the stem cell niche, almost nothing is known about a potentially similar role of hypoxia in maintaining the tumor stem cell (TSC) niche. Here we show that a highly tumorigenic fraction of side population (SP) cells is localized in the hypoxic zones of solid tumors in vivo. We first identified a highly migratory, invasive, and tumorigenic fraction of posthypoxic side population cells (SPm [hox] fraction) in a diverse group of solid tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
293
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 278 publications
(308 citation statements)
references
References 61 publications
(97 reference statements)
11
293
1
3
Order By: Relevance
“…Previous studies [20,22] have demonstrated that sidepopulation cells of the SK-NB-BE(2) NB cell line and tumor-initiating human NB cells express the embryonic stem cell [12][13][14] and cancer stem cell marker Oct-4 [15][16][17][18][19][20]. The human Oct-4 gene can generate at least three transcripts (Oct-4A, Oct-44B and Oct-4B1) and four protein isoforms (OCT4A, OCT4B-190, OCT4B-265 and OCT4B-164) by alternative splicing and alternative translation initiation [31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies [20,22] have demonstrated that sidepopulation cells of the SK-NB-BE(2) NB cell line and tumor-initiating human NB cells express the embryonic stem cell [12][13][14] and cancer stem cell marker Oct-4 [15][16][17][18][19][20]. The human Oct-4 gene can generate at least three transcripts (Oct-4A, Oct-44B and Oct-4B1) and four protein isoforms (OCT4A, OCT4B-190, OCT4B-265 and OCT4B-164) by alternative splicing and alternative translation initiation [31].…”
Section: Discussionmentioning
confidence: 99%
“…All isotypic controls used for immunofluorescence tested negative ( Figure 2B Figure S1, 4,8,12,16,20).…”
Section: Identification and Immunophenotypic Characterization Of Oct-mentioning
confidence: 99%
See 2 more Smart Citations
“…Given the role of SP and ALDH functionalities in HSC quiescence/self-renewal [14,[38][39][40], reflecting two processes involved in early stem cell regulation, the isolation of cells expressing both activities is of great interest to better understand these processes. Furthermore, because SP and ALDH are involved in stem cell multidrug resistance [41], this coupled technology is of clinical significance, allowing the comparison, quantification, and manipulation of normal and leukemic stem cells (LSCs) [39]. Actually, it is hypothesized that LSCs are quiescent and closely associated with a specific niche environment, from which they can be forced to escape to expose them to antileukemic drugs [42].…”
Section: Discussionmentioning
confidence: 99%